1999
DOI: 10.2337/diacare.22.9.1517
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenetic analysis suggests different pathogenesis for obese and lean African-Americans with diabetic ketoacidosis.

Abstract: Our results indicate that most obese African-American patients with DKA have type 2 diabetes characterized by higher insulin secretion, the absence of autoimmune markers, and a lack of HLA genetic association. In contrast, most lean African-American patients with DKA have metabolic and immunological features of type 1 diabetes. At presentation, assessment of beta-cell function and determination of autoimmune markers allow for correct classification of diabetes in African-Americans with hyperglycemic crises.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
74
2
12

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(98 citation statements)
references
References 3 publications
10
74
2
12
Order By: Relevance
“…Banerji et al (2) reported a higher frequency of HLA DR3/DR4 in GAD65 autoantibodynegative African-American patients with type 2 diabetes (65%) compared with nondiabetic control subjects (30%). Umpierrez et al (6) reported that all those with GAD autoantibodies in a cohort of predominantly African-American KPD patients possessed the DQB1*0201 allele. Wang et al (34) found that the frequency of the autoimmune type 1 diabetes susceptibility genotype DR3-DQ2/ DR4-DQ8 was 10-fold higher and that of the protective allele DQB1*0602 10-fold lower among newly diagnosed younger children with autoantibodies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Banerji et al (2) reported a higher frequency of HLA DR3/DR4 in GAD65 autoantibodynegative African-American patients with type 2 diabetes (65%) compared with nondiabetic control subjects (30%). Umpierrez et al (6) reported that all those with GAD autoantibodies in a cohort of predominantly African-American KPD patients possessed the DQB1*0201 allele. Wang et al (34) found that the frequency of the autoimmune type 1 diabetes susceptibility genotype DR3-DQ2/ DR4-DQ8 was 10-fold higher and that of the protective allele DQB1*0602 10-fold lower among newly diagnosed younger children with autoantibodies.…”
Section: Methodsmentioning
confidence: 99%
“…etosis-prone diabetes (KPD), an emerging form of diabetes defined by presentation with diabetic ketoacidosis (DKA) (1)(2)(3)(4)(5)(6)(7), is phenotypically heterogeneous (1)(2)(3)(4)(5)(6). KPD patients may have variable ␤-cell function and clinical outcomes after the initial presentation with DKA.…”
mentioning
confidence: 99%
“…Patients with ketosis-prone type 2 diabetes were once described as having "atypical diabetes;" however, increasing evidence indicates that this subtype of diabetes accounts for more than half of newly diagnosed black and Hispanic patients with DKA (3,6,17,42,43). These subjects are usually obese, have a strong family history of diabetes, have a low prevalence of autoimmune markers, and lack HLA genetic association (9 …”
Section: E D I T O R I a L S E D I T O R I A L ( S E E B A L A S U B mentioning
confidence: 99%
“…For this test, C-peptide levels are measured before and within 10 min after the intravenous administration of glucagon (1 mg) (6,7,10). In agreement with this report, fasting C-peptide levels Ͼ1.0 ng/dl (0.33 nmol/l) and stimulated Cpeptide levels Ͼ1.5 ng/dl (0.5 nmol/l) shortly after presentation is predictive of long-term remission (6 -8,10,12,14, 36,37).…”
Section: E D I T O R I a L S E D I T O R I A L ( S E E B A L A S U B mentioning
confidence: 99%
“…Latent autoimmune diabetes is not plausible since late appearance of islet-cell autoimmunity has not been reported. Obesity, which is an exceptional finding in classic Type I diabetes, is found in up to 56 % of the cohorts of patients with this atypical presentation [8] and mean BMI varies between 26 and 37 kg/m 2 [1,2,9,10].…”
mentioning
confidence: 99%